FORMATION OF THE RESTORATION SCHOOL IN UZBEKISTAN AND ITS ROLE IN PRESERVATION OF ARCHITECTURAL HERITAGE - Makhmudova, Malika; Makhmudova, Muhayyo (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The article considers the history of the origination of the restoration of the architectural heritage in Uzbekistan, the formation of a scientific methodology for the restoration of architectural monuments.Also, the article is devoted to the formation of the restoration school of Uzbekistan, information about the well-known architects-restorers and scientists who stood at the origins of the restoration work in the republic, such as M.F. Mauer, B.N. Zasypkin and others, as well as examples from their restoration practice is given in the article.The analytical method, generalization methods, systematization and practical experience were used in the article. In particular, the following were studied: (1) literature on the restoration of architecture in Uzbekistan, materials from the Central State Archives of Architecture of Uzbekistan, materials of the personal achieves of restorers; (2) practical experience of architects in the restoration of architectural monuments; (3) object of study: architectural heritage of Uzbekistan: minarets, mausoleums, mosques, madrasahs and other types of architectural objects; (4) subject of research: structures, domes, architectural decor of interiors and facades of monuments of architecture, as well as the activities of renowned architects-restorers and scientists of Uzbekistan.